On Matching Teacher’s Teaching Styles with Student’s Learning Styles - Novalita Fransisca Tungka (Sintuwu Maroso Journal of English Teaching, 2017)
A mismatch between students’ learning styles and teacher’s teaching styles can cause ineffective instructional activities to happen. To avoid that, a teacher must be informed about students’ behaviors in the classroom that shape one’s learning styles, and use such information to develop teaching styles that are compatible with students’ learning styles. This paper discusses about the spectrum of learning styles and its impact on teaching styles taken from the perspectives of Lawrence’s and Grasha’s explanations and theories on teaching styles and their implications to classroom instructions. Suggestions of instructions that match learning styles and teaching styles and to overcome teacher’s resistance to modify one’s teaching styles are presented. The discussions and suggestions made contribute to instructional theories.Keywords: learning styles, teaching styles, instruction